Relationship of hepcidin with Iron and lipids in patients with polycystic ovary Syndrome - Sherin Bahgat Ayed AL- Tikriti; Nazar Ahmed Naji (Tikrit Journal of Pure Science)
polycystic ovary Syndrome is a common disorders in the endocrine glands in woman reproductive age the ovary is characterized by the aggregation of small bags surrounded by theca interna layers bloated follicles .